Assessing Technologies: Global Patterns of Trust and Distrust. Report on one session at the XVIII World Congress of Sociology - António Moniz (Technikfolgenabschätzung – Theorie und Praxis, 2015)
Technology assessment (TA) had never been treated as a relevant topic within the International Sociological Association (ISA) before. The first steps towards establishing this association were taken in 1948, at the initiative of the Social Science Department of UNESCO. Its formal foundation was in 1949. The World Congress of Sociology in Japan was hopefully the beginning of continuous integration of TA into the thematic sessions within the ISA.
http://www.tatup-journal.de/english/tatup151_moni15a.php
Keywords: O33; Y80; 330; Technology assessment; ISA; UNESCO; Trust; STS